Developmental shape changes in facial morphology: Geometric morphometric analyses based on a prospective, population-based, Chinese cohort in Hong Kong - Wen, Yi Feng (PLoS One, 2019)
BACKGROUND: Thorough understanding of developmental changes of human facial shape is lacking. The present study aimed to evaluate developmental shape changes of facial morphology based on a prospective, population-representative, Chinese cohort in Hong Kong. METHODS: A population-representative sample of Chinese in Hong Kong was followed. Serial facial images of over 260 participants were obtained at age 12, 15, and 18 years. Facial landmarks were digitized and the corresponding coordinates were submitted for Generalized Procrustes Analysis. The resultant Procrustes shape coordinates, which captured shape information encoded by the facial landmarks, were then used for statistical shape analyses. RESULTS: Small but significant developmental changes in mean facial shape were observed (p < 0.0001 for all pairwise comparisons). Significant age-related changes in the magnitude of variance of facial shape were also observed (p < 0.05). Phenotypic growth trajectories representing developmental shape changes were similar in size (p > 0.05) between sexes but differed in direction (p < 0.05) in shape space and trajectory shape (p < 0.05). The magnitude of shape differences between sexes remained constant from 12 to 18 years. Results of frontal facial shape analyses after removing the effect of allometry were similar to results obtained before removal of allometry. For lateral facial configurations, allometric trajectories among the age-by-sex groups were similar in slope (p > 0.05) but varied in directions in the multidimensional shape space. CONCLUSIONS: Our findings suggested significant age-related changes in facial shape and provided a dynamic view of developmental changes in sexual dimorphism of facial shape. Allometry contributed minimally to developmental changes in frontal facial shape. In addition, the allometric trajectories for lateral facial configurations were similar in rate of shape change but differed in their directions in shape space.